The Effect of Fasting Ramadhan on Malondialdehyde Levels Stress Oxidative Paramater in Obese Patient - Ginting, Septi Nina Maria; Melati Silvanni Nasution (TALENTA Publisher, Universitas Sumatera Utara, 2020)
Obesity induces the formation of reactive oxygen species (ROS) which is produce oxidative stress that is involved in various pathological processes such as malondialdehyde (MDA) which is a highly toxic molecule. In Indonesia, Muslims are fasting for 13-14 hours during Ramadhan. Researchers interested in conducting research on the effect of fasting Ramadhan on oxidative stress (MDA levels) in individuals with obesity. This research is a prospective cohort. The study was held on March – May 2019 at Outpatient Clinic Endocrinology of RSUP. H. Adam Malik Medan with the approval of the FK USU Research Ethics Commission and according to the criteria of inclusion and exclusion. The Data is analyzed by using the SPPS program where p < 0.05 is considered significant. The results of the study obtained a meaningful decline in the level of MDA before and after the fasting of Ramadhan (p < 0.001). The median rate of MDA before Ramadhan was 4.88 nmol/ml (1.68-101,5 nmol/ml) and after Ramadhan fasting the median rate of MDA became 3.96 nmol/ml (0.97-92,20 nmol/ml). There was decreased of oxidative stress parameter MDA levels after Ramadhan fasting in obese patients.